Práticas anticompetitivas no mercado de trabalho: impactos no direito do trabalho brasileiro - David, Mariana Piva Zadra (2022)
This research provides an overview of the practices with anti-competitive potential in the labor market, adopted by Human Resources departments, as a consequence of the abuse of the employer authority and economic power, and the potential impacts regarding the Brazilian Labor Law and the protection of the employees’ rights. In Brazil, the debate on the intersection between Labor Law and Antitrust is quite preliminary, even though in recent years the Administrative Council for Economic Defense (Cade) indicated that the labor market studies have been identified as a topic of relevant impact. In the vanguard of such studies are the United States (US), and the analysis of the most relevant cases brought in that jurisdiction made possible the reflection on the impacts of anti-competitive practices based on the differences on the labor markets of developed countries (US) and countries that are in development (Brazil). Furthermore, on the practical level, there are few studies on the effective legal impacts related to practices that may restrict salaries and the mobility of employees in the Brazilian labor market. Therefore, due to the importance of the debate, the absence of in-depth discussions and the possible lack of knowledge of Brazilian Human Resources professionals on the subject and its legal impacts, the study and guidelines suggestions aims to advise companies how to avoid or mitigate the risks of future questioning, under the scope of Brazilian antitrust and labor law.